Copy number of P elements, KP/full-sized P element ratio and their relationships with environmental factors in Brazilian Drosophila melanogaster populations - Ruiz, M. T.; Carareto, CMA (Nature Publishing Group, 2003)
The P transposable element copy numbers and the KP/full-sized P element ratios were determined in eight Brazilian strains of Drosophila melanogaster. Strains from tropical regions showed lower overall P element copy numbers than did strains from temperate regions. Variable numbers of full-sized and defective elements were detected, but the full-sized P and KP elements were the predominant classes of elements in all strains. The full-sized P and KP element ratios were calculated and compared with latitude. The northernmost and southernmost Brazilian strains showed fewer full-sized elements than KP elements per genome, and the strains from less extreme latitudes had many more full-sized P than KP elements. However, no clinal variation was observed. Strains from different localities, previously classified as having P cytotype, displayed a higher or a lower proportion of KP elements than of full-sized P elements, as well as an equal number of the two element types, showing that the same phenotype may be produced by different underlying genomic components of the P-M system.
Keywords: P transposable elements; KP elements; KP/full-sized P elements; P-M systems; Drosophila melanogaster